Typologies of knowledge: a reexamination from the perspective of cognitive materialism. (1st March 2017) - Zukerfeld, Mariano
Abstract : The aim of this paper is to reexamine some typologies of knowledge as a means of framing the presentation of our own typology, which arises from a particular theoretical framework – cognitive materialism. In a somewhat arbitrary route through the economics of innovation, organizational and management studies, the typologies of Lundvall, Machlup, Mokyr, Spender, Blackler and Chartrand are reviewed and criticized. Then, picking up on some elements which arise from the previous analysis, the proposal of a cognitive materialist typology is introduced, based on distinguishing types of knowledge on the basis of the material medium or bearer in which they exist. A division into four types is suggested: knowledge with a biological, subjective, inter-subjective and objective bearer, each with its own respective sub-types.